PENGARUH PEMBIAYAAN BAGI HASIL, PEMBIAYAAN JUAL BELI, DAN INTELLECTUAL CAPITAL TERHADAP KINERJA KEUANGAN BANK SYARIAH INDONESIA - Hardiansyah, Dicky Chandra; Hayati, Sirrul (Universitas Islam Negeri Mataram, 2024)
The aim of this research is to find out the impact of the financing of income, sales and sales financing, and intellectual capital on the financial performance of Shariah Bank Indonesia. The aim of this research uses quantitative research because the data used is in the form of numbers using a multiple linear regression approach. The data used is a time series, namely data on musyarakah profit sharing financing, murabahah buying and selling financing, intellectual capital, and financial performance with the ROA indicator. The data used is secondary data via the official BSI website. Meanwhile, data analysis techniques use classic assumption tests, multiple linear regression tests, and hypothesis testing. The results of this research show that musyarakah profit sharing financing has no effect on BSI's financial performance, murabahah buying and selling financing has no effect on BSI's financial performance, and intellectual capital has a significant effect on BSI's financial performance.